Development of an Augmented Reality Application for Chemistry Molecule Learning in Inclusive Schools - Ramadhani, Fajar; Satria, Bagus; Imron, Imron; Junirianto, Eko; Maria, Eny (Sebatik, 2024)
Education for Special Needs Children (SNC), particularly those on the autism spectrum, requires unique and tailored teaching methods due to significant differences in their learning processes compared to typical children. The use of appropriate teaching tools and media is essential to help children with autism better understand learning materials, including Chemistry lessons in inclusive schools. One promising approach is the development of learning tools based on computer vision technology. This technology can assist SNC students and teachers in teaching chemical concepts through three-dimensional objects, making the teaching and learning process more effective and engaging. This research aims to integrate real objects with virtual elements in Chemistry learning environments at inclusive schools using augmented reality (AR) and image-tracking technology. The learning process will occur in real-time, enabling students with special needs to interact more intensively with the subject matter. The long-term goal of this research is to evaluate the positive impact of AR on improving SNC students' learning outcomes in Chemistry. The results of this research are expected to contribute to the application of AR technology in Chemistry education at inclusive schools, enhancing inclusivity and effectiveness in the learning process.